An Interdisciplinary Open Elective Course Learning & Employment Benefits: A case study on Green Building Course - Vamsi Krishna, B.; Sudhakara Reddy, S.; Prasanna Kumar, R. (Journal of Engineering Education Transformations, 2018)
Choice Based Credit System (CBCS) is widely being practiced by many institutions in India since it has become signatory of the University Grants Commission (UGC). This has promoted in such away that different open elective courses should be offered by every department in engineering to other departments. This interdisciplinary of learning open elective courses by other department students especially in engineering education will have learning awareness and job oriented benefits. Choice based credit system is one of them. Engineering students require the opportunity to choose any open elective course from different departments and apply their knowledge to acquire jobs in that field of course. Learning and employment benefits are not only through their own course subjects but also through open elective courses. In this paper an attempt is made to analyze the various factors affecting the choice of an open elective by the students, to enhance teaching, learning and employment opportunities. In the present case study the subject green buildings offered by civil engineering department at our college to the students of other branches was taken as reference. It was observed that most of the CSE Students have shown enormous interest in choosing this subject for various reasons.All these factors associated with the selection of this subject by the CSE students is carefully evaluated and analyzed through qualitative and quantitative approach.